2007
DOI: 10.1088/0031-9155/53/1/004
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterization of a novel electronic brachytherapy system

Abstract: The Axxent developed by Xoft Inc. is a novel electronic brachytherapy system capable of generating x-rays up to 50 keV. These low energy photon-emitting sources merit attention not only because of their ability to vary the dosimetric properties of the radiation, but also because of the radiobiological effects of low energy x-rays. The objective of this study is to characterize the x-ray source and to model it using the Geant4 Monte Carlo code. Spectral and attenuation curve measurements are performed at variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 24 publications
1
38
0
1
Order By: Relevance
“…This source exhibited depth dose behavior similar to low-energy photon-emitting low dose rate sources 125 I and 103 Pd, yet with capability for variable and much higher dose rates, and subsequently adjustable pe netration possibilities. Liu et al [14] performed the spectral and attenuation curve measurements to characterize it in terms of spectrum and half-value layers. The change in beam quality due to source to source variation and source aging is significant, and each source should be treated on individual basis.…”
Section: Purposementioning
confidence: 99%
“…This source exhibited depth dose behavior similar to low-energy photon-emitting low dose rate sources 125 I and 103 Pd, yet with capability for variable and much higher dose rates, and subsequently adjustable pe netration possibilities. Liu et al [14] performed the spectral and attenuation curve measurements to characterize it in terms of spectrum and half-value layers. The change in beam quality due to source to source variation and source aging is significant, and each source should be treated on individual basis.…”
Section: Purposementioning
confidence: 99%
“…; who measured the HVL at 0.5 ± 0.2 mmAl, using a similar, modified TG‐61 setup 8. Table 2 shows that the attenuation by Tegaderm are all less than 0.4% for the four different methods accounting for changing energy spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al. concluded that the change in beam quality due to source variation and source aging is significant and each source should be treated on an individual basis 8. Independent verification and validation of all equipment and software provided by vendor is of upmost importance for accuracy of treatment and patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…The 192 Ir spectrum was taken from National Nuclear Data Center (Baglin 2012) and the 50 kV spectrum from Liu et al (2008) using a Geant4 model based on the work of Rivard et al (2006). Additionally, simpler geometries such as a water cube and a spherical APBI applicator were employed for estimation of calculation efficiency and validation.…”
Section: Geometries Of Interestmentioning
confidence: 99%